Kemampuan Literasi Saintifik Siswa SMA pada Materi Optik Geometri - Tuti Resri Yanti; Lia Yuliati; Hari Wisodo (Pascasarjana Universitas Negeri Malang, 2019)
Abstract: The trend of 21st century education is learning based on scientific literacy. Scientific literacy is a key for improving science education in many countries in the world. This article aims to give a profile of the scientific literacy of senior high school students of class XII in the year 2019 in optic subject. This research was conducted with Survey methods. The data is done by providing scientific literacy problem in the form of essays. The subjects of research is the students of class XII at two SMAN Kerinci Regency. Results of this research is scientific literacy of students still low. So that Indonesia can afford prices in the era of the 21st century education, thope that this research can help in determining the solution for improve the ability of students ' scientific literacy. Abstrak: Tren pendidikan abad-21 adalah pembelajaran yang berpatokan pada Literasi Saintifik yang dijadikan sebagai kunci utama dalam meningkatkan pendidikan sains di banyak Negara di dunia. Artikel ini bertujuan untuk memberikan gambaran tentang kemampuan Literasi Saintifik siswa SMA kelas XII pada tahun 2019 terhadap materi Optik. Penelitian ini dilakukan dengan metode survei. Teknik pengambilan data dilakukan dengan memberikan soal literasi saintifik yang berbentuk esai. Subjek penelitian adalah siswa-siswa kelas XII di dua SMAN yang ada di kabupaten Kerinci. Hasil penelitian menunjukkan bahwa literasi saintifik siswa masih rendah. Agar Indonesia mampu bersaing di era pendidikan abad-21, diharapkan penelitian ini dapat memberikan solusi dalam meningkatkan kemampuan literasi saintifik siswa.